Critical Discourse Analysis of Moral Values in EFL Textbook for Senior High School - M.A. Silmi Mahrudin; Didin Nuruddin Hidayat; Nida Husna; Alek Alek (Al-Lisan: Jurnal Bahasa, 2023)
This study aims to determine the description of the moral values contained in the English textbook for class XI Senior High School, which the Ministry of Education and Culture of the Republic of Indonesia approved. The present study uses Critical Discourse Analysis (CDA) with a qualitative design method. This study uses critical discourse analysis to determine the moral values in visual and verbal texts. The study found the English textbook contains moral values in behaving in the surrounding environment, both in individual and in groups. Another thing is that most of what is listed in this English textbook contains moral values such as a sense of responsibility for oneself and others. The other findings, a sense of concern for the surrounding environment and concern for others, are described from visual and verbal texts. Thus, the moral values found in this textbook need to be known by teachers and students so that they can think more critically and read about understanding moral values such as a sense of responsibility, care, and concern.